Adaptasi Dan Transformasi Lagu Adat Dalam Liturgi Gereja Katoli K Di Manggarai Flores (Universitas Gadjah Mada, 2020)
Manggarai, a community in Flores, Eastern Indonesia is known for its rich culture of folk songs with unique rhythm and lyrics. There are various types of folk songs for different purposes such as traditional chants, harvest celebrations, lamentation of the dead, war anthems, children songs, and other profane functions. When European missionaries started Catholic vangelization in Manggarai in the beginning of the 20th century, many of these folk songs were prohibited due to their use in rituals deemed idolatry. However, some missionaries saw the potential of folk songs for evangelization and empowered local artists to arrange Catholic liturgical songs based on these traditional songs. Eventually, many folk songs were adapted and transformed into Catholic hymns. This paper explores this irony through socio-historical research to understand the relationship dynamics between the Catholic Church and the Manggaraianculture. This research has discovered that there is a dialectical encounter between Catholicism and the Manggaraian culture which has shaped a unique identity of the Catholic Church in Manggarai.